2022
DOI: 10.1200/go.22.00024
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We Dying? Ethnic Differences in Place of Death Among New Zealanders Dying of Cancer

Abstract: PURPOSE Around a third of people with cancer will die outside of their preferred place of death, with substantial variation occurring between and within countries in terms of place of death. Here, we examine place of death within the New Zealand cancer context, with specific focus on differences between Indigenous Māori and other ethnic groups. METHODS Using national-level data, we identified all those who died in New Zealand between 2007 and 2018 of cancer (N = 107,373), stratified by ethnicity and cancer typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Older people who were Aboriginal and/or Torres Strait Islander were also less likely to die in ED in our study. Other studies have found a greater likelihood to die in a private residence for Māori people [ 50 ] and a preference to die ‘on country’, surrounded by family and friends for Aboriginal and/or Torres Strait Islander people [ 51 ]. Our finding suggests that these preferences may have been translated somewhat into the care received in this cohort’s EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Older people who were Aboriginal and/or Torres Strait Islander were also less likely to die in ED in our study. Other studies have found a greater likelihood to die in a private residence for Māori people [ 50 ] and a preference to die ‘on country’, surrounded by family and friends for Aboriginal and/or Torres Strait Islander people [ 51 ]. Our finding suggests that these preferences may have been translated somewhat into the care received in this cohort’s EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing – Most research into ethnicity and palliative care that has taken place in the USA, the UK, Australia and New Zealand is based largely on the comparative architecture and present data that invariably use the ‘white’ population, albeit unintentionally, as the standard. 31,32,53,82,109115 This racial and ethnic nomenclature has the potential to lead to the phenomena of ethnocentricity or an inherent predisposition to view a single and often the majority culture as the standard against which others are or should be judged. 116 This has consequences for many aspects of palliative care research where ethnicity is a focus.…”
Section: The Potential To Cause Harmmentioning
confidence: 99%